Orthodontics : principles and practice - Gill, Daljit S.; Naini, Farhad B. (Chichester, West Sussex : Wiley-Blackwell, 2011)
'Orthodontics: Principles and Practice is the latest in the Dental Update books series, offering a clear and comprehensive guide to contemporary orthodontic practice. Offering a highly practical clinical manual format, it covers patient assessment, diagnosis and treatment planning of both standard class malocclusions and specific entities (such as impacted teeth, digit sucking habits and asymmetries) appliance techniques, complex and multidisciplinary care, and retention'--Provided by publisher.
Orthodontics: Principles and Practice; Contents; Contributors; Preface; 1: Growth and Development; 1: An introduction to human craniofacial growth and development; 2: Development of the dentition; 2: Diagnosis and Treatment Planning; 3: Aetiology of malocclusion; 4: Patient assessment; 5: Facial aesthetics: historical and theoretical considerations; 6: Smile analysis; 7: The psychology of facial appearance; 8: Orthodontic records; 9: Cephalometric analysis; 10: Space planning for the dentition (space analysis); 11: The index of orthodontic treatment need.
Includes bibliographical references and index.
Print version record.
Keywords: Orthodontics; Orthodontics; Electronic books